Strategic Narratives for Global Brands: Crafting Cross-Cultural Communication in the Digital Era (Revista Interdisciplinar de Marketing, 2025)
Social media have disrupted corporative global communication and marketing practices, providing valuable opportunities for global engagement, customer relations, and brand promotion. This study investigates how companies develop and apply social media strategies, adjusting them to different markets and cultural contexts. To this end, we develop a four-phase empirical analysis, using qualitative and quantitative approaches, on Instagram strategies of five global brands - Samsung, McDonald's, Coca-Cola, Starbucks, and IKEA - in ten different countries. Results indicate that global brands thrive by balancing global consistency with local presence and relevance, paying attention to cultural content adaptation, linguistic nuances, and consumer preferences in each market they operate. This strategy ultimately promotes consumer loyalty, as they can relate to the brand and feel it is an integral part of their communities and daily lives. Findings contribute to understanding digital marketing in global branding and offer practical insights for companies looking to navigate the complexities of cultural diversity in their social media strategies.